My Problem is this given System of differential equations.

$$y_{1}^{\prime}=5y_{1}+2y_{2} \\ y_{2}^{\prime}=-2y_{1}+y_{2}$$

I am looking for the solution. According to one of my earlier Questions, I tried the method on my own. Now i fear the solution could be wrong. (especially the eigenvectors)

My Approach was: again, i analyze, it must be a ordinary, linear System of equations, with both being of first-order. Than i built the corresponding Matrix as follows:

$$\underbrace{\pmatrix{ y_1^{\prime} \\ y_2^{\prime}}}_{\large{ {\vec y^{\prime}}}} = \underbrace{\pmatrix{5 & 2 \\ -2 & 1}}_{\large{\mathbf A}}\underbrace{\pmatrix{y_1\\y_2}}_{\large{\vec y}}$$

that's why:

$$\vec y^{\prime} = \pmatrix{5 & 2 \\ -2 & 1}\vec y$$

Then I determined the eigenvalues:

they are $r_1 = 3$ and $r_2=3$

Knowing them, I can build the corresponding eigenvectors:

they are $\vec v_1 = \pmatrix{ -1 \\ +1}$ and $\vec v_2 = \pmatrix{ 0 \\ 0}$

Now i plug into the equation:

$$\vec{x} = c_1e^{r_1t}\vec{v_1}+c_2e^{r_2t}\vec{v_2} \\ \vec{x} = c_1e^{3t}\pmatrix{-1 \\ 1}+c_2e^{3t}\pmatrix{0 \\ 0}$$

this lead to my result:

$$y_1 = -c_1e^{3t} + 0c_2e^{3t}\\ y_2 = c_1e^{3t} + 0c_2e^{3t} \\ \\ y_1 = -c_1e^{3t}\\ y_2 = c_1e^{3t}$$

But I doubt it's correct. My suspect are the eigenvectors, I really don't know if they are correct. And this could have lead to a wrong solution.

P.S.: Edits were made to improve language and latex

  • 2
    $\begingroup$ This obviously wrong since you can't take the zero vector as an eigenvector. $\endgroup$ – user63181 Jul 2 '13 at 7:51
  • $\begingroup$ You don't need the zero eigenvector. Look at my answer here. $\endgroup$ – Kw08 Jan 22 '17 at 7:17

Hint:$$X '(t)=AX(t)$$ if you have repeated eigen value like $ c $ and $v $ is eigen vector correspond to $c $ then general solution is $$\large{X(t)=e^{ct}v}$$ and here solution is:$$\large{ X(t) = ce^{3t}\pmatrix{-1 \\ 1}}$$



You calculated the double eigenvalue correctly, but you cannot have a zero eigenvector as that is not allowed.

You should have done:

$[A - \lambda I]v_1 = 0$ to find the first eigenvector and then $[A- \lambda I]v_2 = v_1$ to find a second generalized eigenvector. You end up with:

  • $\lambda_1 = 3, ~v_1 = (-1, 1)$
  • $\lambda_2 = 3, ~v_2 = (-\dfrac{1}{2}, 0)$

Since we have a repeated eigenvalue, our solution will be written as:

$$Y(t) = c_1 e^{\lambda_1 t} v_1 + c_2 e^{\lambda_2 t}(v_1t + v_2) = c_1e^{3t} \begin{bmatrix}-1\\1\end{bmatrix} + c_2 e^{3t}\left(t\begin{bmatrix}-1\\1\end{bmatrix} +\begin{bmatrix}-\dfrac{1}{2}\\0\end{bmatrix}\right)$$

I would recommend reviewing this in your book as it is critical to understand.

  • $\begingroup$ Nice work, and recommendation! ;-) $\endgroup$ – amWhy Jul 3 '13 at 0:10

Found this one sitting around on my laptop, and realized I'd never posted it; better late than never, I guess! Here goes:

Not to put too fine a point on it, but Maisim Hedyelloo's answer does not tell the whole story. True, the eigenvalues of the matrix $A$ are the repeated pair 3, 3; this follows from the fact that the characteristic polynomial of $A$ is

$\det(A - \lambda I) = \det(\begin{bmatrix} 5 - \lambda & 2 \\ -2 & 1 - \lambda \end{bmatrix}) = (5 - \lambda)(1 - \lambda) + 4 = \lambda^2 - 6\lambda + 9= (\lambda - 3)^2$,

which easily seen to have root $\lambda = 3$ of multiplicity $2$. Now consider the matrix $N$ defined by the equation

$2N = A - \lambda I = A - 3I = \begin{bmatrix} 2 & 2 \\ -2 & -2 \end{bmatrix} = 2 \begin{bmatrix} 1 & 1 \\ -1 & -1 \end{bmatrix}$,

so that

$N = \begin{bmatrix} 1 & 1 \\ -1 & -1 \end{bmatrix}$.

A simple calculation reveals that

$N^2 = 0$,

i.e., $N$ is nilpotent of degree $2$; hence $2N$ is as well: $(2N)^2 = 4N^2 = 0$. Next, we recall that for any initial vector $y(0) = y_0$, the solution to the ODE is $y(t) = e^{At}y_0$; and, based upon what we have done already, the matrix exponential $e^{At}$ is easily had. Note that, by the above, $A = 3I + 2N$, so that

$e^{At} = e^{(3I + 2N)t}$.

At this point, the critical step is to observe that

$e^{(3I + 2N)t} = e^{3It}e^{2Nt}$;

this equation between the matrix exponentials on either side holds by virtue of the fact that the two matrices $3I$ and $2N$ commute; that is $(3I)(2N) = (2N)(3I)$, or, if you prefer the bracket notation, $[3I, 2N] = 0$. Under these circumstances, it can be shown that the rule $e^{X + Y} = e^Xe^Y$ holds for matrices exactly as it does for ordinary real or complex numbers. In the present case of course the relation $(3I)(2N) = (2N)(3I)$ or $[3I, 2N] = 0$ is trivially obvious, since one of the matrices in question is a scalar multiple of the identity matrix $I$; but the result is quite general. A full discussion and proof may be found in Hirsch, Smale, and Devaney's Differential Equations, Dynamical Systems, and an Introduction to Chaos, Second Edition, Elsevier Academic Press, 2004, pp. 123-130. In any event we can now conclude that

$e^{At} = e^{3It}e^{2Nt}$,

and since it is evident that $e^{3It} = e^{3t}I$, we further have

$e^{At} = e^{3t}Ie^{2Nt} = e^{3t}e^{2Nt}$

so all we really need to do is evaluate $e^{2Nt}$; but this is easy: since $N^2 = 0$, the power series expansion of $e^{2Nt}$ is truncated after the first-degree term, hence we have

$e^{2Nt} = I + 2Nt$,


$e^{At} = e^{3t}e^{2Nt} = e^{3t}(I + 2Nt)$.

It is now a relatively simple matter to write down the solution which passes through the point $y_0 = (y_{01}, y_{02})^T$ at the time $t = 0$. Since

$I + 2Nt = \begin{bmatrix} 1 + 2t & 2t \\ -2t & 1 - 2t \end{bmatrix}$,

we have

$y(t) = e^{At}y_0 = e^{3t}(I + 2Nt)y_0 = e^{3t}\begin{pmatrix}y_{01} + 2t(y_{01} + y_{02}) \\ y_{02} - 2t(y_{01} + y_{02})\end{pmatrix}$

$= e^{3t}\begin{pmatrix}y_{01} \\y_{02}\end{pmatrix} + (y_{01} + y_{02})te^{3t}\begin{pmatrix} 2 \\ -2 \end{pmatrix}$;

it is easy to verify, by a direct and elementary computation, that such $y(t)$ satisfies $y'(t) = Ay(t)$ with $y(0) = y_0$. Examining this equation, we observe that in the event that $y_{01} + y_{02} = 0$, i.e. $y_{01} = -y_{02}$ the solution $y(t) = e^{3t}(y_{01}, y_{02})^T = e^{3t}(y_{01}, -y_{01})^T = y_{01}e^{3t}(1, -1)^T$ is in fact of the general form suggested by Maisam Hedyelloo in his answer; but this is indeed a very special solution, lying as it does in the unique, one-dimensional eigenspace of $A$ generated by the eigenvector $(1, -1)^T$. In general we should expect $y_{01} + y_{02} \ne 0$, in which case the solution contains a (vector) term proportional to $te^{3t}$. We can re-write $y(t)$, thus:

$y(t) = e^{3t}\begin{pmatrix}y_{01} \\y_{02}\end{pmatrix} + (y_{01} + y_{02})te^{3t}\begin{pmatrix} 2 \\ -2 \end{pmatrix}$ $= e^{3t}\begin{pmatrix} y_{01} \\ -y_{01}\end{pmatrix} + e^{3t}\begin{pmatrix} 0 \\ y_{01} + y_{02}\end{pmatrix} + (y_{01} + y_{02})te^{3t}\begin{pmatrix} 2 \\ -2 \end{pmatrix}$ $= y_{01}e^{3t}\begin{pmatrix} 1 \\ -1\end{pmatrix} + (y_{01} + y_{02})e^{3t}\begin{pmatrix} 0 \\ 1\end{pmatrix} + 2(y_{01} + y_{02})te^{3t}\begin{pmatrix} 1 \\ -1 \end{pmatrix}$ $= (y_{01}+ 2(y_{01} + y_{02})t)e^{3t}\begin{pmatrix} 1 \\ -1\end{pmatrix} + 2(y_{01} + y_{02})e^{3t}\begin{pmatrix} 0 \\ \frac{1}{2}\end{pmatrix}$,

which exhibits the complete solution in terms of a component lying in the unique eigenspace of $A$, spanned by $(1, -1)^T$, and a component $2e^{3t}(y_{01} + y_{02})(0, \frac{1}{2})^T$ which lies in the one-dimensional subspace spanned by the generalized eigenvector $(0, \frac{1}{2})^T$. The fact that Amzoti's choice of generalized eigenvector, $(-\frac{1}{2}, 0)^T$, is different that the present one, $(0, \frac{1}{2})^T$, yet still yields a valid solution is, I believe, explained by the fact that there is a certain latitude in the choice of the generalized eigenvector $v_2$ corresponding to the eigenvector $v_1$ via the formula $(A - \lambda)v_2 = v_1$, for if we add a scalar multiple of $v_1$ to $v_2$ we still obtain a generalized eigenvector satisfying the equation $(A - \lambda)v = v_1$: taking $v = v_2 + \alpha v_1$ we see that

$(A - \lambda)(v_2 + \alpha v_1) = (A - \lambda)v_2 + \alpha(A - \lambda)v_1= v_1$

by virtue of the fact that $(A - \lambda)v_1 = 0$; if we now observe that $(\frac{1}{2}, 0)^T = (0, \frac{1}{2})^T + \frac{1}{2}(1, -1)^T$ we see that the apparent discrepancy between Amzoti's choice of generalized eigenvector and mine is resolved. (Note: Amzoti chooses $(-1, 1)^T$ for the eigenvector and $(-\frac{1}{2}, 0)^T$ for the generalized eigenvector, which is consistent with our choice of eigenvector $(1, -1)$ since eigenvectors are, shall we say, scale invariant; that is, $Av = \lambda v$ if and only if $A(\alpha v) = \lambda (\alpha v)$ for $\alpha \ne 0$.)

In the development I have given here, I have used the concepts of nilpotence and the nilpotent part $2N = A - \lambda I$ of the matrix $A$ in lieu of the more conventional methodology which exploits generalized eigenvectors; such an approach makes the direct calculation of $\exp{At}$ simple, as has been seen above. It is in fact the nilpotent part of $A$, $2N$, which gives rise the generalized eigenvectors since $(A - \lambda)v_2 = 2Nv_2 = v_1$, and we have seen that it is the nilpotent part which gives rise to the terms of the functional form $te^{3t}$ in our solution. Such terms may also be derived via generalized eigenvectors directly, as is well-known, and has been mentioned by Amzoti in his/her answer. All of this machinery of course generalizes to higher dimensions; but the discussion of such matters would take us even further afield, and I have, for the moment, written enough. I hope these words are graced to bring with them a little of what Henry Jones, Sr., sought in, if I am not mistaken, Raiders of the Lost Ark, and that is: illumination.

Fiat Lux!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.